Mathematics game following KSSR for primary school student - Lee, Shin Yee (2014)
The main purpose and user requirement of this project is to develop a Mathematics educational game as additional learning tool for primary school student. The gameplay that designed and created is applying the Mathematics knowledge to real world situation and makes learning mathematics become more interactive. Besides that, the gameplay designed is also following KSSR Mathematics syllabus from MOE. The game system is developed using Unity3D with JavaScript. The question of each game level are created randomly so that the question generate for every each session are different. To ensure the functional of this educational game, the functionality of each feature was tested. Moreover, user acceptance test were conducted to get the satisfaction from the target users which include the children, teachers and parents.